2016
DOI: 10.1016/j.aott.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness of kyphoplasty and vertebroplasty in patients with osteoporotic vertebra fractures

Abstract: ObjectiveThe aim of this study was to compare the functional and radiological outcomes of vertebroplasty and kyphoplasty in patients with osteoporotic vertebra fractures.MethodsThe files of the patients who underwent vertebroplasty or kyphoplasty for osteoporotic vertebrae fractures were retrieved from the archives. Forty-three patients with complete follow-up data were included in the study group. The patients were evaluated for radiological outcomes in terms of local kyphosis angle, wedging index, compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…VP and KP can be considered when pain remains or progressive vertebral collapse occurs even after conservative treatments are performed. VP and KP for OVCF are all effective, while KP is effective for reduction of vertebral body height, but there is no significant difference in pain control between VP and KP 3 , 5) . Some reported that when an IVC sign is present, polymethyl methacrylate (PMMA) is not an appropriate scaffolding for the fractured vertebral body as PMMA cannot be interdigitated with the trabeculae of the vertebral body, because the fibrocartilaginous membrane is formed inside the IVC, resulting in vertebral compression fracture, which makes intravertebral PMMA be dislodged to the spinal canal, possibly causing neurologic compromise 18) .…”
Section: Treatmentmentioning
confidence: 91%
See 2 more Smart Citations
“…VP and KP can be considered when pain remains or progressive vertebral collapse occurs even after conservative treatments are performed. VP and KP for OVCF are all effective, while KP is effective for reduction of vertebral body height, but there is no significant difference in pain control between VP and KP 3 , 5) . Some reported that when an IVC sign is present, polymethyl methacrylate (PMMA) is not an appropriate scaffolding for the fractured vertebral body as PMMA cannot be interdigitated with the trabeculae of the vertebral body, because the fibrocartilaginous membrane is formed inside the IVC, resulting in vertebral compression fracture, which makes intravertebral PMMA be dislodged to the spinal canal, possibly causing neurologic compromise 18) .…”
Section: Treatmentmentioning
confidence: 91%
“…It is known that the difference in the effectiveness of VP and KP is not significant, and the correction of kyphotic angle is better in KP than VP, without much significance 3 , 5) . It was suggested that it is important to fully fill the cavity using sufficient PMMA by increasing the size of IVC and restoring vertebral body height with the inducement of hyperlordosis during surgery, and it is meaningful to use a cavitogram to check the process 13) .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…5–7 Surgical treatments include percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP). 810 The bone cement distribution in vertebral augmentation is related to the treatment effect, 1113 but the influence of the type of distribution of bone cement along the fracture line on the curative effect is rarely reported. Therefore, the present study focused on the effects of different types of bone cement distribution along the fracture line on pain relief, bone cement leakage, recovery from vertebral compression, and other parameters in patients with OVCFs.…”
Section: Introductionmentioning
confidence: 99%
“…The local kyphosis angle (KA) was 15.3±11.4 before the procedure and 8.02±2.9 after the procedure (P<0.005). In previously published studies, restoration of VHR with kyphoplasty was reported to be 12.8–31.7% and the KA correlation was 3.9–16.5° [ 11 13 ]. In these previous studies, the lowest KA cure rate was reported in patients with rheumatoid arthritis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%